On the craft of almotacé in the city of Lisbon (18th century) - Ferreira, Paulo da Costa (2014)
After establishing an historical contextualization from references to the curule aedile of the Roman Empire, the islamic muthasib and the Ordenações do Reino (Ordinances of the Kingdom), the present article establishes the positioning of almotacé in Lisbon during the 18th century, in terms of its attributions, career access path, mandate duration and renewal, as well as the remuneration, tracing a characterization framework of the craft in its fundamental features and background.